Meningkatkan Kemandirian Minat Baca Siswa Metode PBL Materi Gereja Sebagai Umat Allah Fase F SMKS Yapim Biru-Biru - Sriwati Br Barus (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Reading holds an important social role in human life. By reading, people may enrich their spirit since their insight becoming wider than before. The first function of reading is as a tool of communication within the society. Through the reading, someone’ background can be also reflected. It also preserved a long-life time achievement. Another aspect of reading is the two different polars can be maintained. The first pole is that reading acts as an important union since it can give moral values. One the other side, it is able to stimuli and produce the constructive and discontructive pollar. Learning process cannot be separated from reading activity, such as review the prior material or even the supporting materials. It is also needed to complish the assignment given. The problem may arise from the students’ interest. It is caused by the lack of the students’ comprehension including the mastery of vocabulary in order to fulfil the goal. Based on the reasons above, it is noted if reading is an important activity must be considered. Reading is a tool to elevate the students’ knowledge – if he/she is a teacher- it is needed to apply their knowledge in the future.